The Influence of Education on Knowledge about Corticosteroid Use at Pharmacy X in Bekasi Regency: Pengaruh Pendidikan terhadap Pengetahuan Tentang Penggunaan Kortikosteroid di Apotek X Kabupaten Bekasi - Rohenti, Iin Ruliana; Fitria, Shela; Yanti, Silfera Indra; Idris, Dewi Yuliana; Wardhani, Meissy Kusuma (Akademi Farmasi Bumi Siliwangi, 2026)
Corticosteroids are a common drug used by the general public. They are very popular because they can suppress the symptoms of a disease. Understanding the public's level of knowledge regarding safety, side effects, and contraindications is crucial when using corticosteroids. However, long-term use or inappropriate dosage can cause unwanted side effects, which is why education about corticosteroids is crucial. To identify patient sociodemographics, analyze knowledge levels before and after education, and analyze the impact of corticosteroids on patients at Pharmacy X in Bekasi Regency. This was a quasi- experimental study with a sample size of 171 people. A 10-question corticosteroid knowledge questionnaire was used, obtained from research journals. The questionnaire was analyzed using normality tests and the Wilcoxon test. The highest sociodemographic data for respondents was 27-35 years old (42.1%), female (52.6%), high school education/equivalent (99%), private/state employees (128%), income >2,500,000 – 3,500,000 (40.4%), and no comorbidities (59.1%). The level of knowledge was poor in the pretest and good in the posttest. The results of the effect of education on the level of knowledge about corticosteroid drugs with a p-value of 0.001% indicate that there is an effect of education on corticosteroid drug use using leaflets on the level of knowledge about corticosteroid drug use.